EFFECTS OF WASTE CROSSED-LINKED POLYETHYLENE ELECTRICAL WASTE COATING ON THE PROPERTIES OF BITUMEN - Adinoyi Abdulfatai, Murana; Rabi’u , Ibrahim; SULEIMAN, ABDULHAKEEM (FUDMA JOURNAL OF SCIENCES, 2023)
The high cost of construction materials and increased axle loads has motivated researchers to seek alternative cost-effective materials for road construction. Studies on the use of waste thermoplastic polyethylene material to improve bitumen properties have been investigated. However, few studies on the use of thermoset polyethylene (cross-linked polyethylene) to modify bitumen have been carried out. This research investigated the use of waste cross-linked polyethylene (XLPE) cable coating on bitumen properties. An FTIR analysis carried out on waste XLPE cable coating revealed that it is predominantly composed of XLPE material. A comparative study carried out on the bitumen properties revealed that the modifier had a decreasing effect on its penetration and ductility but, had an increasing effect on softening point and specific gravity; Hence, a considerable improvement in the temperature susceptibility and stability of the bitumen. The short-term ageing analysis carried out revealed that the modified bitumen can withstand short-term ageing requirements at 2% and 4% by weight of pure bitumen. FTIR analysis carried out on the pure and modified bitumen revealed that changes observed in bitumen properties with increasing modifier content were a result of physical changes and not chemical changes. A one-way ANOVA carried out on the properties of various bitumen content revealed that the modifier had a significant effect on the properties of pure bitumen with increasing bitumen content. The regression models developed properly described the relationship between the modifier content and the bitumen properties as they expressed very good R2 values.
Keywords: XLPE electrical cable coatings; Consistency; Short term ageing; FTIR analysis